Beneficio de los enraizantes en la propagación vegetativa de esquejes de Caña guadúa (Guadua angustifolia) en el Ecuador - Zambrano Gaibor, Feiber Dussey (2020)
This document was developed with the purpose of studying the benefits of rooting in the vegetative propagation of cuttings of Caña guadúa (Guadua angustifolia) in Ecuador. The objectives were to collect documentation on the rooting in the vegetative propagation of cuttings and establish the benefits of the rooting in the vegetative propagation of cuttings of Caña guadúa. The realization of this practical document was made based on the compendium of texts, magazines, newspapers, scientific articles, congresses, presentations, internet information. The information was submitted to the analysis technique - synthesis and summary on the benefits of the rooting in the vegetative propagation of cuttings of Caña guadúa (Guadua angustifolia). Based on the information gathered, it was determined that in the agronomic characteristics of plant height, root increase and increase in the thickness of the stem of guadua cane are obtained by applying rooting for the vegetative propagation of cuttings and when using hormone-based rooting, greater production is promoted. Caña guadúa, which will increase the economic benefits of the producers of this crop. The recommendations made were to use rooting products based on hormones to increase crop yields of Caña guadúa (Guadua angustifolia) in Ecuador; promote the use of rooting in the vegetative propagation of cuttings of Caña guadúa and raise awareness among producers about the benefit of rooting in cuttings crops.